Characterization of the Chemical Constituents of Agarwood Oils from Malaysia by Comprehensive Two-Dimensional Gas Chromatography–Time-of-Flight Mass Spectrometry - Saiful Nizam, Tajuddin; M. M., Yusoff; Norfatirah, S. Muhamad; Mohd A., Yarmo (Elsevier, 2013)
4-Phenyl-2-butanone, alpha-bulnesene, alpha-guaiene, agarospirol, ledene oxide-(II), elemol and gamma-eudesmol were identified as the major chemical constituents of Malaysian agarwood oils.